2014
DOI: 10.1128/jcm.03618-13
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mupirocin Resistance in Staphylococcus pseudintermedius

Abstract: In the United States, veterinary use of mupirocin is primarily limited to the treatment of canine pyoderma caused by methicillinresistant Staphylococcus pseudintermedius (MRSP). In this study, only 1 of 581 S. pseudintermedius isolates tested was resistant to mupirocin and carried the high-level mupirocin resistance gene, ileS2, on a plasmid. Staphylococcus pseudintermedius is the primary bacterial pathogen isolated from canine pyoderma and also causes postsurgical infections in dogs (1, 2). Methicillin resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…21 Mupirocin resistance remains rare in S. pseudintermedius, with 1 of 581 isolates exhibiting resistance in a US study. 22 In the current study we identified one isolate displaying mupirocin resistance using the 5-μg disc diffusion method described by Fuchs et al 12 A limitation of this method is that it does not distinguish between low-and high-level mupirocin resistance and has been further refined by a two-disc method. 23 Nevertheless, the discovery of a MRSP strain also exhibiting mupirocin resistance does suggest that, although currently rare, multidrug-resistant isolates are emerging.…”
Section: Discussionmentioning
confidence: 90%
“…21 Mupirocin resistance remains rare in S. pseudintermedius, with 1 of 581 isolates exhibiting resistance in a US study. 22 In the current study we identified one isolate displaying mupirocin resistance using the 5-μg disc diffusion method described by Fuchs et al 12 A limitation of this method is that it does not distinguish between low-and high-level mupirocin resistance and has been further refined by a two-disc method. 23 Nevertheless, the discovery of a MRSP strain also exhibiting mupirocin resistance does suggest that, although currently rare, multidrug-resistant isolates are emerging.…”
Section: Discussionmentioning
confidence: 90%
“…Although this is lower than prevalence rates of High‐Mu r in S. aureus isolates in studies noted above, this rate could increase with continued use of mupirocin ointment in dogs. To date, High‐Mu r S. pseudintermedius isolated from dogs has only been reported in three countries (Croatia, USA and Turkey) . These isolates were obtained from normal nares, a postoperative infection site and a skin infection site.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, mupirocin can eradicate nasal colonization of Staphylococcus aureus . Mupirocin resistance in S. aureus is classified into two types: low‐level mupirocin resistance (Low‐Mu r ) which is caused by a point mutation in the naïve chromosomal ileS gene, and high‐level mupirocin resistance (High‐Mu r ) which is caused by the plasmid‐encoded ileS‐2 which encodes a novel synthetase, thereby inducing mupirocin resistance . In terms of minimal inhibitory concentrations (MIC) for human isolates, ≤4 mg/L is considered to be susceptible to mupirocin, whereas 8–256 and ≥512 mg/L are considered as Low‐Mu r and High‐Mu r , respectively …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations